(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
In addition to a brief introductory study, this paper presents a list of articles published in an illustrated publication Srpkinja: njezin život i rad, njezin kulturni razvitak i njezina narodna umjetnost do danas, which was published in Sarajevo in 1913 by prominent Serbian female writers of the time.